مظاهر التّداخل اللّغوي في أسماء البرامج التّلفزيونيّة الموجَّهة إلى الشّباب الجزائري وانعكاساتها على لغته "مقاربة سوسيولسانيّة" - مطروش, سفيان; عبد الرحمان, حسان (جامعة الوادي - University of Eloued, 2020)
حاولت ورقتنا البحثيّة،الوصول إلى الواقع اللّغوي الذي تشهده لغة الشّباب الجزائري اليوم؛حيث تمّ التّركيز على مدى تأثير وسائل الإعلام المرئيّة على هذا الواقع،والذي تَجسَّد دائما في تقديم العاميّة المحليّة واللّغات الأجنبيّة على حساب اللّغة العربيّة الفصيحة؛ممّا ولَّدَ لغة هجينة جسّدتها مختلف الصّياغات اللغويّة لأسماء العديد من البرامج الموجّهة إلى الشّباب الجزائري. وعليه،اتّخذت الدّراسة من المقاربة "السّوسيولسانيّة" منهجًا،تدرس من خلاله هذه الظّاهرة،وما تحدثه من انعكاسات على اللّغة الشّبابيّة في الجزائر،كما حاولت أيضًا،تشخيص الأسباب التي أدّت إلى استفحالها،والإلمام بأهم الحلول التي لابدَّ لمختلف الهيئات أن ترفعها،من أجل الحدّ منها،والنّهوض بمستوى اللّغة العربيّة عند هذه الفئة المهمّة من المجتمع الجزائري.Our research paper tried to reach the linguistic interference witnessed by the Algerian youth language today. The focus was on the extent of the impact of the visual media on this reality, which was embodied in presenting local colloquial, accents and foreign languages at the expense of eloquent Arabic language, which generated a hybrid language embodied in various formulas Linguistic names of many of the programs targeted at Algerian youth . Accordingly, the study took a "sociological" approach, through which it studied this phenomenon, and its repercussions on the youth language in Algeria. I have also tried to diagnose the reasons that led to its aggravation, and to know the most important solutions those different bodies must raise in order to reduce them, and to improve the level of the Arabic language in this important group of Algerian society.
Aspects Of linguistic Interference In The Names Of Television Programs Directed At Algerian Youthand Its Implications For His Language;"The Sociolinguistic Approach"
مقال
Keywords: تداخل لغوي ، أسماء برامج تلفزيونيّة ، لغة شباب جزائري، مقاربة سوسيولسانيّة.; Linguistic interference, TV program names, Young Algerian language, Sociolinguistic approach.